Common NOTCH3 Variants and Cerebral Small-Vessel Disease. Issue 6 (June 2015) - Rutten-Jacobs, Loes C.A.; Traylor, Matthew; Adib-Samii, Poneh; Thijs, Vincent; Sudlow, Cathie; Rothwell, Peter M.; Boncoraglio, Giorgio; Dichgans, Martin; Bevan, Steve; Meschia, James; Levi, Christopher; Rost, Natalia S.; et al.
Abstract : Background and Purpose—: The most common monogenic cause of cerebral small-vessel disease is cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy, caused by NOTCH3 gene mutations. It has been hypothesized that more common variants in NOTCH3 may also contribute to the risk of sporadic small-vessel disease. Previously, 4 common variants (rs10404382, rs1043994, rs10423702, and rs1043997) were found to be associated with the presence of white matter hyperintensity in hypertensive community-dwelling elderly. Methods—: We investigated the association of common single nucleotide polymorphisms (SNPs) in NOTCH3 in 1350 patients with MRI-confirmed lacunar stroke and 7397 controls, by meta-analysis of genome-wide association study data sets. In addition, we investigated the association of common SNPs in NOTCH3 with MRI white matter hyperintensity volumes in 3670 white patients with ischemic stroke. In each analysis, we considered all SNPs within the NOTCH3 gene, and within 50-kb upstream and downstream of the coding region. A total of 381 SNPs from the 1000 genome population with a mean allele frequency >0.01 were included in the analysis. A significance level of P <0.0015 was used, adjusted for the effective number of independent SNPs in the region using the Galwey method. Results—: We found no association of any common variants in NOTCH3 (including rs10404382, rs1043994, rs10423702, and rs1043997) with lacunar stroke or white matter hyperintensity volume. We repeated our analysis stratified for hypertension but again found no association. Conclusions—: Our study does not support a role for common NOTCH3 variation in the risk of sporadic small-vessel disease. Abstract : Supplemental Digital Content is available in the text.